Localised release of matrix metallopeptidase 8 in fatal cerebral malaria. Issue 4 (29th April 2021) - Georgiadou, Athina; Naidu, Praveena; Walsh, Sophie; Kamiza, Steve; Barrera, Valentina; Harding, Simon P; Moxon, Christopher A; Cunnington, Aubrey J
Abstract: Objective: Cerebral malaria (CM) is a complication of Plasmodium falciparum malaria, in which progressive brain swelling is associated with sequestration of parasites and impaired barrier function of the cerebral microvascular endothelium. To test the hypothesis that localised release of matrix metallopeptidase 8 (MMP8) within the retina is implicated in microvascular leak in CM, we examined its expression and association with extravascular fibrinogen leak in a case–control study of post‐mortem retinal samples from 13 Malawian children who met the clinical case definition of CM during life. Cases were seven children who were found on post‐mortem examination to have 'true‐CM' (parasite sequestration in brain blood vessels), whilst controls were six children who had alternative causes of death ('faux‐CM', no parasite sequestration in blood vessels). Methods: We used immunofluorescence microscopy and independent scoring, by two assessors blinded to the CM status, to assess MMP8 expression, extravascular fibrinogen as an indicator of vascular leak and their co‐localisation in the retinal microvasculature. Results: In 'true‐CM' subjects, MMP8 staining was invariably associated with sequestered parasites and a median of 88% (IQR = 74–91%) of capillaries showed MMP8 staining, compared with 14% (IQR = 3.8–24%) in 'faux‐CM' ( P ‐value = 0.001). 41% (IQR = 28–49%) of capillaries in 'true‐CM' subjects showed co‐localisation of extravascular fibrinogen leak and MMP8 staining, compared with 1.8% of capillaries in 'faux‐CM' (IQR = 0–3.9%, P ‐value = 0.01). Vascular leak was rare in the absence of MMP8 staining. Conclusion: Matrix metallopeptidase 8 was extensively expressed in retinal capillaries of Malawian children with malarial retinopathy and strongly associated with vascular leak. Our findings implicate MMP8 as a cause of the vascular endothelial barrier disruption in CM, which may precipitate fatal brain swelling. Abstract : To test the hypothesis that localised release of matrix metallopeptidase 8 (MMP8) within the retina is implicated in microvascular leak in cerebral malaria (CM), we examined its expression and association with extravascular fibrinogen leak in a case‐control study of post‐mortem retinal samples from 13 Malawian children. MMP8 was extensively expressed in retinal capillaries of children with CM retinopathy and strongly associated with vascular leak. Our findings implicate MMP8 in the vascular endothelial barrier disruption in CM, which may precipitate fatal brain swelling.